Effect of Acupressure Therapy on Low Back Pain among Third-Trimester Pregnant Women - Ermaya Sari Bayu Ningsih; Yuli Erlina; Dina Hartini; Grace Evelyn Malinti (Karya Kesehatan Siwalima, 2025)
Low back pain during pregnancy is defined as pain occurring in the lumbar region, specifically above the sacrum, which may radiate to the legs and increase the risk of low back pain in subsequent pregnancies. This study aimed to determine the effect of acupressure therapy on low back pain among third-trimester pregnant women at Mitra Sehat Clinic, Pabuaran, in 2025. This study employed a quantitative analytical approach with a pre-experimental one-group pretest–posttest design without a control group. The sampling technique used was purposive sampling, involving 30 pregnant women. Data were collected from primary and secondary sources, and the instrument used was a pain scale measurement. Data were analyzed using a paired t-test. The results showed that before receiving acupressure therapy, 22 participants (73.4%) experienced severe low back pain. After the intervention, 19 participants (63.4%) demonstrated a reduction in pain intensity to a moderate level. In conclusion, acupressure therapy has a significant effect on reducing low back pain among third-trimester pregnant women. Pregnant women are encouraged to maintain their health during pregnancy, participate in maternal health classes, and undergo acupressure therapy twice a week to prevent low back pain.